The Dynamic Effects of Personal and Corporate Income Tax Changes in the United States - Mertens, Karel; Ravn, Morten O (American Economic Review, 2013)
This paper estimates the dynamic effects of changes in taxes in the United States. We distinguish between changes in personal and corporate income taxes and develop a new narrative account of federal tax liability changes in these two tax components. We develop an estimator which uses narratively identified tax changes as proxies for structural tax shocks and apply it to quarterly post-WWII data. We find that short run output effects of tax shocks are large and that it is important to distinguish between different types of taxes when considering their impact on the labor market and on expenditure components. (JEL E23, E62, H24, H25, H31, H32)